Structure of Arabidopsis thaliana Rubisco activase. (1st April 2015) - Hasse, Dirk; Larsson, Anna M.; Andersson, Inger
<x xml:space="preserve">Abstract</x> The CO2‐fixing enzyme ribulose‐1, 5‐bisphosphate carboxylase/oxygenase (Rubisco) is inactivated by the formation of dead‐end complexes with inhibitory sugar phosphates. In plants and green algae, the ATP‐dependent motor protein Rubisco activase restores catalytic competence by facilitating conformational changes in Rubisco that promote the release of the inhibitory compounds from the active site. Here, the crystal structure of Rubisco activase from Arabidopsis thaliana is presented at 2.9 Å resolution. The structure reveals an AAA+ two‐domain structure. More than 100 residues in the protein were not visible in the electron‐density map owing to conformational disorder, but were verified to be present in the crystal by mass spectrometry. Two sulfate ions were found in the structure. One was bound in the loop formed by the Walker A motif at the interface of the domains. A second sulfate ion was bound at the N‐terminal end of the first helix of the C‐terminal domain. The protein packs in a helical fashion in the crystal, as observed previously for Rubisco activase, but differences in the helical pitch indicate flexibility in the packing of the protein.